Language of the gun youth, crime, and public policy - Harcourt, Bernard E., 1963- (Chicago, [Ill.] ; London : University of Chicago Press, 2006)
The author recounts interviews with youths in an all-male correctional facility, exploring how they talk about guns and what meanings they ascribe to them in an attempt to understand some of the assumptions implicit in current handgun policies. He redraws the relationships among empirical research, law, and public policy.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Catalina Mountain School; Juvenile delinquents -- Arizona -- Tucson -- Attitudes; Firearms -- Social aspects; Youth and violence; Firearms and crime; Firearms ownership -- United States; Gun control -- United States; Social sciences -- Philosophy; Politics and Government; United States of America, USA; Society & culture: general; Violence in society; Sociology & anthropology; Jurisprudence & general issues